Utilization of PET-CT in target volume delineation for three-dimensional conformal radiotherapy in patients with non-small cell lung cancer and atelectasis - Yin, Li-Jie; Yu, Xiao-Bin; Ren, Yan-Gang; Gu, Guang-Hai; Ding, Tian-Gui; Lu, Zhi (Multidisciplinary Respiratory Medicine, 2013)
Background: To investigate the utilization of PET-CT in target volume delineation for three-dimensional conformal radiotherapy in patients with non-small cell lung cancer (NSCLC) and atelectasis.Methods: Thirty NSCLC patients who underwent radical radiotherapy from August 2010 to March 2012 were included in this study. All patients were pathologically confirmed to have atelectasis by imaging examination. PET-CT scanning was performed in these patients. According to the PET-CT scan results, the gross tumor volume (GTV) and organs at risk (OARs, including the lungs, heart, esophagus and spinal cord) were delineated separately both on CT and PET-CT images. The clinical target volume (CTV) was defined as the GTV plus a margin of 6-8 mm, and the planning target volume (PTV) as the GTV plus a margin of 10-15 mm. An experienced physician was responsible for designing treatment plans PlanCT and PlanPET-CT on CT image sets. 95% of the PTV was encompassed by the 90% isodose curve, and the two treatment plans kept the same beam direction, beam number, gantry angle, and position of the multi-leaf collimator as much as possible. The GTV was compared using a target delineation system, and doses distributions to OARs were compared on the basis of dose-volume histogram (DVH) parameters.Results: The GTVCT and GTVPET-CT had varying degrees of change in all 30 patients, and the changes in the GTVCT and GTVPET-CT exceeded 25% in 12 (40%) patients. The GTVPET-CT decreased in varying degrees compared to the GTVCT in 22 patients. Their median GTVPET-CT and median GTVPET-CT were 111.4 cm3 (range, 37.8 cm3-188.7 cm3) and 155.1 cm3 (range, 76.2 cm3-301.0 cm3), respectively, and the former was 43.7 cm3 (28.2%) less than the latter. The GTVPET-CT increased in varying degrees compared to the GTVCT in 8 patients. Their median GTVPET-CT and median GTVPET-CT were 144.7 cm3 (range, 125.4 cm3-178.7 cm3) and 125.8 cm3 (range, 105.6 cm3-153.5 cm3), respectively, and the former was 18.9 cm3 (15.0%) greater than the latter. Compared to PlanCT parameters, PlanPET-CT parameters showed varying degrees of changes. The changes in lung V20, V30, esophageal V50 and V55 were statistically significant (Ps< 0.05 for all), while the differences in mean lung dose, lung V5, V10, V15, heart V30, mean esophageal dose, esophagus Dmax, and spinal cord Dmax were not significant (Ps> 0.05 for all).Conclusions: PET-CT allows a better distinction between the collapsed lung tissue and tumor tissue, improving the accuracy of radiotherapy target delineation, and reducing radiation damage to the surrounding OARs in NSCLC patients with atelectasis.